Uroprotective and Hepatoprotective Potential of Anagallis arvensis against the Experimental Animal Model - Ushna Shabbir; Irfan Anjum; Muhammad Naveed Mushtaq; Muhammad Nasir Hayat Malik; Sana Ismail; Joham Javed; Saeeda Noreen; Ayesha Pervaiz; Anika Tariq; Misbah Wazir; Zeenat Islam; Muhammad Majid; et al. (Journal of Tropical Medicine)
Anagallis arvensis (A. arvensis) belonging to the family Primulaceae is traditionally used for liver and kidney diseases. The aim of the study was to evaluate the uroprotective and hepatoprotective potentials of A. arvensis in cyclophosphamide-induced interstitial cystitis and paracetamol-induced hepatotoxicity rat model, respectively. Nociception, bladder weight, vesical vascular permeability, Gray’s criteria for edema and hemorrhage, and levels of nitric oxide, catalase, and glutathione were estimated and studied in the cystitis model. Liver function test, lipid profile, and histopathological evaluation were carried out in the hepatoprotective activity. Oral administration of methanol extract of A. arvensis significantly reduced bladder weight, vesical vascular permeability, edema, hemorrhage, nitric oxide, IL-6, and TNF-α, while the level of catalase and glutathione peroxide was increased. In hepatoprotective activity, pretreatment with A. arvensis significantly decreased the level of liver markers (Bilirubin, ALT, AST, and ALP) and lipid profile (cholesterol, TG, LDL, and VLDL). Histopathological studies confirmed the biochemical findings of both studies. GC-MS analysis presented the presence of antioxidant phytoconstituents. Thus, it was concluded that A. arvensis might act as uroprotective and hepatoprotective due to the presence of antioxidant phytochemicals in the rodent model. Isolation and identification of phytochemicals present in the methanol extract of A. arvensis and evaluation of their exact mechanism of action become mandatory in future studies.